Subject and Current Problems of Theolinguistic Research in World Religious Studies - Aliya Kusherbayeva; Ainura Kurmanaliyeva (Pharos Journal of Theology)
This study investigated the subject and current problems of theological linguistics in world religious studies, focusing on the analysis of linguistic units and their role in three key religious texts: the Bible (Christianity), the Quran (Islam), and the Vedas (Hinduism). The purpose of this study was to identify the linguistic features of these texts that influence religious communication, the formation of spiritual beliefs and behavioural patterns of believers. The study also considered how language supports dogmatic positions and shapes the collective identity, which are key aspects of theolinguistic research. The study employed discourse analysis to investigate rhetorical figures, symbols, and functional features of religious language, as well as cognitive analysis to trace the influence of texts on the consciousness, emotional reactions, and behaviour of believers. For the quantitative comparison of lexemes in religious texts, the Mann-Whitney U-test was applied, which helped to assess statistically significant differences between the discourses. In the Christian texts, the study found the dominance of the lexemes “love” (234 cases) and “mercy” (89 cases), which emphasises the moral, ethical, and emotional nature of this tradition. In Islamic texts, the lexemes “obedience” (146) and “justice” (112) are frequent, reflecting the normative nature of Islamic discourse, which is focused on submission to God’s will. The Vedic texts are dominated by the lexemes “dharma” (153) and “karma” (98), which suggests an orientation towards fulfilling duties and spiritual development. The findings demonstrate that each religious discourse contains unique linguistic elements that convey dogmatic statements and form cognitive models that regulate the social behaviour of believers and support collective identity. The study emphasised the significance of theological linguistics as an interdisciplinary field that reveals the relationship between language, culture, and spiritual beliefs.